2000
DOI: 10.1073/pnas.97.20.11032
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal stress produces learning deficits associated with an inhibition of neurogenesis in the hippocampus

Abstract: Early experiences such as prenatal stress significantly influence the development of the brain and the organization of behavior. In particular, prenatal stress impairs memory processes but the mechanism for this effect is not known. Hippocampal granule neurons are generated throughout life and are involved in hippocampaldependent learning. Here, we report that prenatal stress in rats induced lifespan reduction of neurogenesis in the dentate gyrus and produced impairment in hippocampal-related spatial tasks. Pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

38
637
7
25

Year Published

2005
2005
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 926 publications
(721 citation statements)
references
References 45 publications
38
637
7
25
Order By: Relevance
“…Changes in the extent of adult hippocampal neurogenesis are associated with changes in the performance of animals in hippocampus-dependent behavioral tasks [7][8][9][10][11], and a recent study of conditional TLX knockout mice, a gene expressed by adult neural stem cells, suggest a causal link between the performance in specific aspects of behavioral tasks and neurogenesis [12]. Voluntary physical exercise is a consistent and strong modulator of adult hippocampal neurogenesis.…”
Section: Introductionmentioning
confidence: 99%
“…Changes in the extent of adult hippocampal neurogenesis are associated with changes in the performance of animals in hippocampus-dependent behavioral tasks [7][8][9][10][11], and a recent study of conditional TLX knockout mice, a gene expressed by adult neural stem cells, suggest a causal link between the performance in specific aspects of behavioral tasks and neurogenesis [12]. Voluntary physical exercise is a consistent and strong modulator of adult hippocampal neurogenesis.…”
Section: Introductionmentioning
confidence: 99%
“…anomalies à la fois du développement mais aussi des capacités cognitives [26]. Le placenta possède un méca-nisme de protection du foetus vis-à-vis d'un excès de cortisol maternel, qui repose sur sa transformation par la 11 -hydroxystéroïde déshydrogénase.…”
Section: Causes Anténatales D'accouchements Prématurés Intervenant Daunclassified
“…Transient SC35 overexpression coincides with AChE-R/AChE-S dominance in the developing brain Maternal stress during pregnancy was reported to cause long-lasting deleterious effects in the offspring, 6 suggesting that stress affects brain development. Also, we have recently shown that neuronal progenitor cells express both AChE-S and AChE-R, which exert distinct effects on cortical development.…”
Section: Sc35 Shifts Ache's Alternative Splicing Towards Ache-r In Trmentioning
confidence: 99%
“…5 In rats, both adult and prenatal stress reduce learning performance, 6 suggesting, among other possibilities, parallel stress-induced changes in alternative splicing. However, the molecular mechanisms leading to such changes are still largely obscure.…”
mentioning
confidence: 99%